'My children are my world': Raising the voices of birth mothers with substantial experience of counselling following the loss of their children to adoption or foster care. (July 2019) - Morgan, Hannah CM; Nolte, Lizette; Rishworth, Barbara; Stevens, Clarissa
There is very little published literature on 'what works' in terms of support for birth mothers following the loss of their children to compulsory adoption or foster care. The aim of this article is to raise the voices of a group of birth mothers, a historically stigmatised, powerless and neglected group, with substantial experience of counselling following the loss of a child. A user of services and expert by experience was recruited to join the research team and was consulted at all stages of the research process. Five birth mothers were interviewed regarding their experiences of involvement with a counselling service for birth relatives post-child removal. These interviews were systematically analysed using an IPA methodology through the lens of the research question: What are the experiences of birth mothers who engage in person-centred counselling following the loss of a child or children to compulsory adoption or foster care? Three master themes were constructed from the data: 'From feeling alone, judged and let down … to feeling part of a special relationship', 'The healing process' and 'My children are my world'. The clinical invitations extended by these findings are discussed.